Liquisolid Lipid Based Liquisolid Compacts of Olmesartan Medoxomil with Improved Oral Bioavailability: In Vitro and In Vivo Evaluation - Dhiraj Chopra (Journal of Global Pharma Technology, 2019)
The main objective of the current research work is to evaluate the potential of lipid based liquisolid compacts (OLC) to enhance oral bioavailability of Olmesartan Medoxomil (BCS Class II molecule).OLC have been prepared using Capmul MCM and Captex as non-volatile vehicles, Pearlitol SD 200, Avicel PH 102 and Flowlac 90 as carrier’s materials and Syloid® 244FP as a coating material. Liquisolid compacts were prepared by premixing the non-volatile liquid and drug in equal ratio, converting the resulting wet mass into free flowing powder using carrier and coating material (5:1 ratio). Prepared LBLC’s were evaluated for their micromeritics properties, solubility, dissolution and in vivo bioavailability in selected rats. Among the formulations prepared, formulation (OLC1) containing Capmul MCM as vehicle, Pearlitol SD 200 as carrier has shown enhanced drug release (99.7 ± 5.4 release in 30 minutes) and solubility (72.54mg/mL) compared to other formulations. Hence, this formulation is evaluated for comparative in vivo bioavailability in rats along with pure drug and marketed formulation (Olmezest). It was found that relative bioavailability of OLC 1 was increased by 4.86 times compared to pure drug and increased by 1.42 times compared to marketed formulation. Hence, the study demonstrated that lipid based liquisolid technology can lead to improve the bioavailability of poorly soluble drugs like olmesartan medoxomil significantly.